Implementasi Algoritma Constraint Satisfaction Problems dan Backtracking Pada Penjadwalan Kegiatan Belajar Mengajar - Zahidah, RA. Ghina; Raissa Amanda Putri (METIK JURNAL (AKREDITASI SINTA 3), 2025)
Technology has brought significant changes to the field of education, including in the management of school activity schedules. At SMP Negeri 27 Medan, the scheduling of teaching and learning activities is still carried out manually using spreadsheets and paper-based records, which takes approximately 1–2 weeks, is prone to errors, and makes it difficult to update schedules in case of sudden changes. This study proposes the development of a web-based scheduling information system using the Constraint Satisfaction Problem (CSP) approach combined with the Backtracking algorithm based on Depth-First Search (DFS). The original contribution of this research lies in the implementation of the combined CSP and DFS methods to fully automate the scheduling process efficiently, which has not been comprehensively applied in previous studies. The research method used is qualitative, with data collection techniques including observation, interviews, and literature study. The system is developed using the Waterfall model, with PHP as the programming language, Laravel for the backend, React JS for the frontend, and MySQL as the database. The implementation results show that the system can automatically generate conflict-free schedules, improve efficiency, flexibility, and accuracy in the scheduling process, and facilitate real-time information access through a web platform that can be accessed by the school, students, and the public.